A 1030 nm all-PM SESAM mode-locked dissipative soliton fiber oscillator and its amplification with Yb-doped fiber and a Yb:YAG thin rod. (1st October 2022) - Kim, Jun Wan; Park, Seolwon; Kim, Guang-Hoon; Yashin, Vladimir E; Yang, Juhee
Abstract: In this research, an all- polarization-maintained semiconductor saturable absorber mirror (SESAM) mode-locked fiber oscillator and its amplification by Yb-doped fiber and a Yb:YAG thin rod are presented. From a ring-type cavity configuration created with commercially accessible components, including SESAM, the dissipative soliton fiber oscillator exhibits stable mode-locking near 1030 nm. Subsequent three-stage fiber amplifiers pumped by single-mode fiber-coupled laser diodes and a single-stage Yb:YAG thin-rod amplifier boost the output power to 11.3 W at a repetition rate of 495 kHz. After pulse compression, a pulse duration of 758 fs is achieved with output power and pulse energy levels of 9 W and 18.2 μ J, respectively.